Roasting Experiment of Cashew Nut on Traditional Industry - Susilo, Bambang (Fakultas Teknologi Pertanian Universitas Brawijaya, 2000)
Processing of cashew nut in Indonesia is worked by small industries, that need relative small energy input. The stages of traditional process of cashew nut comprise:drying of cashew, shelling of pericarp, frying without oil, shelling of epidermis, dryingand grading. In this research a roasting experiment of cashew nut were carried out as pretreatmentbeforeshellingactivity.Thispre-treatmentintendedtoextracttheCashewNutShellLiquid (CNSL) content in shell. By this treatment the shell will be brittle and theshelling capacity in traditional process is also increased. This pre-treatment is alsoincreased the whole kernel as indicator of the quality of cashew nut product. The effect of roasting as pre-treatment on shelling capacity shows that the roastingcan increase the shelling capacity. The average of shelling capacity increases morethan100 % i.e. from 4,5 kg/hour to 9,5 kg/hour. This treatment is also increase the wholekernel. By the usual shelling the average whole kernel is 62,17 % and by the treatment itfound 82,9 % or increased 33,5 %. The colour of the nut product visually is not differentby the usual shelling and the treatment. Technically the roasting activity enables to be applied in traditional processing ofcashew nut especially for the small industries.Keyword: cashew nut, roasting, and traditional industry